The hidden colours of vape - Look, Keyun; Ser, Hooi Leng *; Amar, Daud Iskandar Abdullah *; Elil, Renganathan *; Long, Chiau Ming* (CodeBlue, 2023)
Our study on 28 vape liquids sold in Malaysia showed that nearly all products (27 of 28) contained added colours. However, none disclosed the presence of colours on their labels. All samples contained flavouring agents, but only 86% stated this on labels.